2016
DOI: 10.1155/2016/5371050
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and Cell Type-Specific Telomere Length Changes in Subsets of Lymphocytes

Abstract: Telomeres, the protective DNA-protein complexes at the ends of linear chromosomes, are important for genome stability. Leukocyte or peripheral blood mononuclear cell (PBMC) telomere length is a potential biomarker for human aging that integrates genetic, environmental, and lifestyle factors and is associated with mortality and risks for major diseases. However, only a limited number of studies have examined longitudinal changes of telomere length and few have reported data on sorted circulating immune cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 45 publications
3
64
0
Order By: Relevance
“…A limitation of our study is that we are not able to pinpoint whether malaria has a synchronized effect on cellular aging markers in all cell types or whether there are specific effects on certain cell subtypes. Nonetheless, telomere length measured in total peripheral blood mononuclear cells (PBMCs) has been shown to be highly correlated to different cell subtypes, and to be highly synchronized in monocytes, T cells, and B cells in healthy individuals (Lin et al., 2016). Furthermore, it has also been shown that there is a synchrony in telomere length and telomere loss in adult mammals and humans (Daniali et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is that we are not able to pinpoint whether malaria has a synchronized effect on cellular aging markers in all cell types or whether there are specific effects on certain cell subtypes. Nonetheless, telomere length measured in total peripheral blood mononuclear cells (PBMCs) has been shown to be highly correlated to different cell subtypes, and to be highly synchronized in monocytes, T cells, and B cells in healthy individuals (Lin et al., 2016). Furthermore, it has also been shown that there is a synchrony in telomere length and telomere loss in adult mammals and humans (Daniali et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This variability may be due to the fact that we did not differentiate between lymphocyte types. Indeed, telomere dynamics differ not only among leucocyte types (as we considered here) but also among lymphocyte types (Weng, ; Lin, Cheon, & Brown, ). However, in Soay sheep, this methodological refinement led to weaker relationships between lymphocyte types and telomere length than the simple correlation between lymphocyte proportion and telomere length (Watson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies on HIV elucidated the link between chronic infection and telomere attrition in CD4 + and CD8 + T cells 23 24. The replicative senescence of T lymphocytes is not limited to HIV since it is broadly investigated in association with malignancies,25 autoimmune disorders26 and environmental mediators 27 28. In autoimmune diseases, telomere erosion in lymphocytes has been less well delineated.…”
Section: Discussionmentioning
confidence: 99%